Financial Sector Inefficiencies and the Debt Laffer Curve - Agénor, Pierre-Richard; Aizenman, Joshua (World Bank, Washington, D.C., 2013)
The authors analyze the implications of inefficient financial intermediation for dbt management, using a model in which firms rely on bank credit to finance their working capital needs, and, lenders face a high state verification and enforcement costs of loan contracts. Their analysis shows that lower expected productivity, higher contract enforcement, and verification costs, or higher volatility of productivity shocks may shift the economy to the wrong side of the debt Laffer curve, with potentially sizable output, and welfare losses. The main implication of this analysis is that debt relief may generate little welfare gains, unless is accompanied by reforms aimed at reducing financial sector inefficiencies.